Implementation of Electronic Traffic Law Enforcement to Improve Traffic Safety in the Special Region of Yogyakarta - Lidya Daryati Angeli Sagala (Green Publisher Indonesia, 2025)
The implementation of Electronic Traffic Law Enforcement (ETLE) in the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta (DIY)) is an effort to digitize traffic law enforcement to reduce violations and accidents. However, despite the program's implementation in 2021, the number of accidents and traffic violations continues to increase year after year. This study aims to evaluate the effectiveness of ETLE, identify barriers to its implementation, and provide strategic recommendations to improve traffic safety in the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta (DIY)). This research uses a qualitative descriptive approach to describe the implementation of ETLE in the Special Region of Yogyakarta in depth by utilizing primary data from interviews, observations, and documentation, as well as secondary data in the form of supporting documents and statistics. Data analysis was conducted using an Interactive Analysis Model that includes data collection, reduction, presentation, and drawing conclusions, supported by Duncan's Effectiveness Measurement Theory and fishbone diagram analysis. Credibility testing was carried out through extended observations, triangulation, negative case analysis, and the use of references to ensure the research results were accurate, valid, and accountable. The research results show that the implementation of ETLE in the Special Region of Yogyakarta remains ineffective in reducing traffic accidents, despite its effective mechanisms. ETLE plays a significant role in identifying violations, but its widespread implementation is still hampered by factors such as workforce, technology, methods, and measurement. Therefore, 12 strategic recommendations are needed to optimize ETLE and improve traffic safety in the Special Region of Yogyakarta.